The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15537/smj.2018.12.23430
|View full text |Cite
|
Sign up to set email alerts
|

Risk of potential drug-drug interactions in the cardiac intensive care units

Abstract: Objectives:To identify and compare the prevalence of drug-drug interactions (DDIs) in the intensive cardiac care units (CCUs) of 2 tertiary care hospitals and analyze their association with various predictors.Methods:This one-year prospective cross-sectional study was conducted in 2 tertiary care hospitals of Peshawar, Khyber Teaching Hospital (KTH) and Hayatabad Medical Complex (HMC), Peshawar, Pakistan, between January 2014 to Janury 2015. The patient medication profiles from the respective CCUs were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 17 publications
(18 reference statements)
9
18
0
Order By: Relevance
“…Such results are similar to those of international research studies in the specialty of cardiology, which point to a frequency of serious interactions ranging from 30% to 86%, polypharmacy as a risk factor for interactions, and anticoagulants, antiplatelet agents, and statins as the main classes involved in interactions (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Such results are similar to those of international research studies in the specialty of cardiology, which point to a frequency of serious interactions ranging from 30% to 86%, polypharmacy as a risk factor for interactions, and anticoagulants, antiplatelet agents, and statins as the main classes involved in interactions (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 87%
“…In one, it was sought to identify drug-drug interactions in patients admitted to cardiac intensive care units in two tertiary hospitals in Pakistan, subsequently comparing the prevalence of these interactions. 260 patients from each hospital who had been hospitalized for at least 24 hours were included, most of them diagnosed with myocardial infarction (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no studies correlating the Brazilian system used to classify patients according to the degree of dependence on nursing with risk of pDDIs; however, previous studies have shown that critical care patients are at increased risk of pDDIs because they present with severe and life-threatening illnesses. Most of them suffer from various comorbidities, and they usually receive complex pharmacotherapy which increases the risk of DDIs [32,3436].…”
Section: Discussionmentioning
confidence: 99%
“…DDI avoidance in this population is critically important as fluctuations in drug concentrations and effects may be particularly harmful to ICU patients 7 . The prevalence of DDIs in intensive care units ranges from 27% to 95% [8][9][10][11] , depending on the ICU setting, study population, hospital's systems for DDI detection, and severity level that is considered a DDI.…”
Section: Introductionmentioning
confidence: 99%